Full Mouth Rehabilitation of a Hypohidrotic Ectodermal Dysplasia Patient with Dental Implants: A Clinical Report - Afsaneh Shahrokhi Rad, DMD, MSc;1 Hakimeh Siadat, DDS, MSc;2 (Journal of Prosthodontics, 2007)
Prosthodontic treatment in patients with ectodermal dysplasia (ED) is difficult to manage because of the oral deficiencies typical in this disorder and because afflicted individuals are quite young when they are evaluated for treatment